2017
DOI: 10.1038/s41598-017-16046-5
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal MRS and subfield volumetry at 7T detects dysfunction not specific to seizure focus

Abstract: Ultra high-field 7T MRI offers sensitivity to localize hippocampal pathology in temporal lobe epilepsy (TLE), but has rarely been evaluated in patients with normal-appearing clinical MRI. We applied multimodal 7T MRI to assess if focal subfield atrophy and deviations in brain metabolites characterize epileptic hippocampi. Twelve pre-surgical TLE patients (7 MRI-negative) and age-matched healthy volunteers were scanned at 7T. Hippocampal subfields were manually segmented from 600μm isotropic resolution suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 61 publications
2
41
0
Order By: Relevance
“…Of note, most studies included in a meta-analysis reported bilateral hippocampal volumes between 4794 mm 3 and 8298 mm 3 (Colle et al, 2018). A similar variation exists for subfields, for example, right CA1 volumes in healthy subjects between 34 and 1635 mm 3 are reported (Sone et al, 2016; Voets et al, 2017).…”
Section: Discussionsupporting
confidence: 68%
“…Of note, most studies included in a meta-analysis reported bilateral hippocampal volumes between 4794 mm 3 and 8298 mm 3 (Colle et al, 2018). A similar variation exists for subfields, for example, right CA1 volumes in healthy subjects between 34 and 1635 mm 3 are reported (Sone et al, 2016; Voets et al, 2017).…”
Section: Discussionsupporting
confidence: 68%
“…As predicted, our results revealed roles for CA1-CA4 and GC-DG, in addition to molecular layer, in the encoding and subsequent retrieval of novel verbal word lists. Several recent studies have provided piecemeal evidence of associations between subfield volumes and verbal episodic memory, implicating subiculum in immediate verbal recall 45 , and CA1 46 , subiculum 46,47 , and presubiculum 45 in delayed verbal recall. Our current IR findings implicate each of the CA subfields and GC-DG, supporting their previously demonstrated roles in encoding of novel stimuli/environments 12,34 , and in verbal and visuo-spatial episodic memory 17,48 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to its location and size, it is technically challenging to acquire high quality 1 H‐MRS spectra in the hippocampal region (Geurts et al, ; Kreis, ; Venkatraman et al, ). Future studies using ultra‐high field 1 H‐MRS (e.g., Voets, Hodgetts, Sen, Adcock, & Emir, ) are now required.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies using ultra-high field 1 H-MRS (e.g., Voets, Hodgetts, Sen, Adcock, & Emir, 2017) are now required.…”
Section: Limitationsmentioning
confidence: 99%